ICT for the EU Multilingualism - Карпчук, Наталія Петрівна; Karpchuk, Nataliia P. (Uniwersytet Mikołaja Kopernika, 2011)
“Multilingualism” is regarded as the ability of communities, groups and individuals to use more than one language on a regular basis in their daily activities, the way to unite “rich in diversity” Europe. ICT can make any necessary information available and accessible, help eliminate language barriers. The European Commission is developing 30 research and innovation projects of language technology which purpose is to help Internet users to get access to the information in their native languages. These projects include the protection of minor languages, the promotion of sign languages, the development of translation technologies.
Keywords: multilingualism; ICT; sign languages; linguistic diversity; on-line translation